Changing the Paradigm of Cancer Screening, Prevention, and Treatment. Issue 4 (29th November 2016) - Doss, Mohan
The war on cancer has been fought during the past several decades primarily based on the somatic mutation model of cancer. This has resulted in the emphasis on cancer screening and elimination of any detected cancerous/precancerous cells as the primary method of cancer prevention. This approach has reduced mortality from some cancers, but age-adjusted cancer mortality rates continue to be high. The lack of significant progress in reducing cancer mortality rates may be indicative of a fundamental flaw in the cancer model used. An alternative model of cancer is the immune suppression model of cancer based on the tremendous increase in cancers when the immune system is suppressed. According to this model, the key carcinogenic event is the suppression of the immune system which enables the already existing covert cancers to grow uncontrollably, causing cancer. Hence, cancer screening would consist of identifying those with weak immune system response. The primary mode of cancer prevention and treatment would be boosting of the immune system, for example, through exercise, infection, and low-dose radiation, as they are all known to enhance immune system response and reduce cancers. There is sufficient evidence to justify clinical trials of this approach for cancer screening, prevention, and treatment.